Non-University Mass Student Public Associations: Institutional Isomorphism as a Factor of Stability - Kashina, M. A.; Popov, V. R. (Upravlencheskoe konsulʹtirovanie, 2022)
The relevance of this research is about the need to search for factors that increase the stability of youth associations, including student ones. Only stable youth associations can effectively socialize young people and form them as active actors in civil society. The project is a desk study and has a quality design. Object: non-university mass student public associations. They were created in Russia in the 60s of the twentieth century: student building brigades (SSO) and student nature protective brigades (DOP). Subject: institutional isomorphism of non-university student public associations. Purpose: to assess the impact of character and the degree of isomorphism of student public associations on their stability. Research results . It is shown that the main factor in the stability of student public associations is the level of their compliance with institutional requirements. It leads to forced isomorphism. The cause of this isomorphism is the monopoly of sources of support for the activities of these associations. In Russia, the state has such a monopoly. Student associations must take into account the institutional factors, in particular the requirements of higher-level systems and institutions. It gives them the necessary resources to continue their activities. Intra-organizational factors (level of social significance, charisma of leaders, mass character, and others) are less important for ensuring their sustainability.